Sociological Understanding of Social Structure and Kin-based Human Behavior - Adhikari, Shukra Raj (GS WOW: Wisdom of Worthy Research Journal, 2024)
The social structure is formed by various elements of society that are interrelated. Within this structure, kinship is considered a micro-social institution by sociologists. This article aims to analyze how different sociological theoretical perspectives explain the social structure and the role and nature of kin-based behavior within it. To achieve this objective, both primary and secondary data were used under the qualitative research approach. Various methods under the qualitative research design were employed, with a focus on autobiography, observation, and content analysis. Primary data was collected through empirical study, using autobiography and observation methods. Secondary data was gathered from sociological references and journal articles based on the thematic categories of theoretical explanations, social structure, and kinship, using the content analysis method. The data was analyzed and presented using content analysis. Within the social structure, the kinship system appears to influence everything from human daily activities to birth, death, status, honor, social and cultural responsibilities, duties, and rights.